The Role of TikTok in Shaping Generation Z’s Slang: Semantic Change and Language Use in Digital Communication - Nashrudina, Pinasti Gemintang Gita; Fajriyah, Ana Muthi'ah; Dewi, Tri Isna (CV. Era Digital Nusantara, 2025)
This study was conducted because of the widespread use of slang among Generation Z children that they use to interact with each other. Slang is a type of informal, non-standard language that is used by certain social groups, particularly teenagers, for internal communication. It is intentionally designed to be unintelligible to those outside the group. Therefore, every community or even every generation has a slang language that is used and understood by their own group. This study aims to examine the slang of Generation Z youth which they use in the TikTok platform based on semantic meaning and context of use. The research approach used is to examine linguistic data in the form of the use of slang by Gen Z youth and interpret it. The source of research data is the result of collecting words from content and comments on the TikTok platform. The results of the study show that the use of slang by Generation Z youth mostly comes from foreign languages, such as ‘slay’, hits different,’ ‘clingy,’ ‘delulu,’ ‘flexing’, that experience shortening, acronyms, reversals, and shifts in semantic meaning based on the context of the words used. Stephen Krashen's theory is also used in this paper to analyze the acquisition of slang used by Generation Z youth. The significance of social media platforms like TikTok as influential sites of language evolution and informal linguistic education, where youth not only consume but actively shape language trends. the study also illustrates how slang serves as a marker of identity, group belonging, and social cohesion among Generation Z, reflecting broader cultural shifts in emotional expression, social relationships, and communication styles